2013
DOI: 10.1186/1472-6963-13-408
|View full text |Cite
|
Sign up to set email alerts
|

An overview of patient involvement in healthcare decision-making: a situational analysis of the Malaysian context

Abstract: BackgroundInvolving patients in decision-making is an important part of patient-centred care. Research has found a discrepancy between patients’ desire to be involved and their actual involvement in healthcare decision-making. In Asia, there is a dearth of research in decision-making. Using Malaysia as an exemplar, this study aims to review the current research evidence, practices, policies, and laws with respect to patient engagement in shared decision-making (SDM) in Asia.MethodsIn this study, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 27 publications
2
69
0
Order By: Relevance
“…A survey in Japan showed that patients there do want to be more involved in healthcare decision-making [21] and new programs have been created in Japan and South Korea. Other Asian countries are challenged by scarce healthcare resources and an overburdened healthcare system [22]. Furthermore, we were still unable to identify any SDM training programs in Africa, India, Russia, South America or China, perhaps an indicator that the approach has not taken hold in these contexts.…”
Section: Discussionmentioning
confidence: 95%
“…A survey in Japan showed that patients there do want to be more involved in healthcare decision-making [21] and new programs have been created in Japan and South Korea. Other Asian countries are challenged by scarce healthcare resources and an overburdened healthcare system [22]. Furthermore, we were still unable to identify any SDM training programs in Africa, India, Russia, South America or China, perhaps an indicator that the approach has not taken hold in these contexts.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed skills training for residents as well as specialists is starting to bud, but mostly so in Western countries such as North-Western Europe, Canada, the US, and Australia [67]. Elsewhere, some groups are active in this field, but the efforts seem incidental so far [68].…”
Section: Discussionmentioning
confidence: 99%
“…This resistance to SDM would hinder the adoption of SDM and subsequently lead to non-use of the insulin PDA. There is a distinct contrast in SDM implementation between developed countries (such as the USA, UK, Germany, Netherlands, Australia, Italy and Spain) where SDM and the use of PDAs have already been implemented at policy and legislation levels [28–31] and developing countries in Asia see slower progress in adopting SDM and PDAs [15, 32]. In Switzerland, however, hierarchical structures and asymmetric physician-patient relationship were reported to be barriers for SDM implementation despite doctors recognizing its importance [31].…”
Section: Discussionmentioning
confidence: 99%
“…The Patient Decision Aids Research Group has created continuous education such as online tutorials, interactive workshops, performance feedback and structured protocols in providing decision support [18]. Efforts are also needed to empower patient in being more involved in their healthcare, and one way to do that is to conduct public health campaigns [15]. In developed countries such as Australia and the UK, the ‘AskShareKnow’ [35, 36] and the ‘Ask three questions’ [37, 38] campaigns are conducted to encourage patients to ask their HCPs the three questions (‘What are my options?’, ‘What are the benefits and harms?’ and ‘How likely are these going to happen?’) to increase patient involvement in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation